(untitled) (Вестник КазНУ. Серия Востоковедения, 2018)
The article deals with the concept of Sufism, as well as its elements and philosophical influence. The significance of Sufism in the formation of Muslim society, as well as the expansion in Central Asia and the stage of development of this trend are analyzed. The role of Sufi orders in the formation of answers to the challenges of the Muslim faith in the modern era is explored. It emphasizes the openness of Sufism for external influence and its end of the Sufi order in modern times. It also mentions the widespread dissemination of mystical ideas through the poetry of Sufi literatures among Muslims, the continuation of Sufi’s responsibility for large-scale missionary activity and political activity of leaders.